The Role of Sensory Marketing in Achieving Customer Patronage in Fast Food Restaurants in Awka - Ifeanyichukwu, Chioma Dili; Peter, Abude (International Research Journal of Management, IT & Social Sciences, 2018)
Sensory marketing is regarded as a new way of making an organizational profit. Less time and more school/work hours have made people pop into a fast food restaurant on a daily basis. More and more restaurants are employing stimuli of Scent, Sound, texture, vision, and taste to build stronger emotional connections with the customer and drive preference to their brand. A quick look at our environment gives one a clearer picture of these fast food restaurants and one begins to wonder why they spring up in great numbers, thus intensifying competition. This study aims at examining the relationship between human senses/ sensory cues and customer patronage. Also, it seeks to find out how fast food restaurants should apply sensory cues to enhance customer patronage. 150 regular customers of Nourisha fast food restaurant in Awka were used as respondents, and a structured questionnaire was administered to elicit the required information from the respondents. Multiple regression was used to test for the significance of the five hypothesis proposed for the study. Results showed the powerful and tremendous effect of the concept of sensory marketing which is inevitable for the success of a firm in this highly competitive market.